Ways of Being Ethnic in Southwest China - Harrell, Stevan (Book collections on Project MUSE., 2001)
Drawing on his field research in southern Sichuan between 1988 and 1994, Harrell (anthropology, U. of Washington) explores how several groups of the region perceive and promote their ethnic identity in different ways and at different times. After setting out the political, natural, and historical contexts, he looks at the primordial ethnicity of the Nuoso, the historically contingent ethnicity of the Prmi and Naze, residual and instrumental ethnicity, and the default ethnicity of the Han. Annotation c. Book News, Inc., Portland, OR (booknews.com).